ENDOSCOPIC TRANSPAPILLARY STENTING OF THE DUCTUS HEPATICOCHOLEDOCHUS IN PATIENTS WITH MECHANICAL JAUNDICE ASSOCIATED WITH TUMORS - Yu. I. Biktagirov; M. L. Shteyner; E. A. Korymasov; E. P. Krivoshchekov; B. M. Rakhimov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Endoscopic interventions have become increasingly popular in the treatment of patients with choledocholithiasis complicated by mechanical jaundice and cholangitis along with conventional surgeries.Objective: to analyze the outcomes of endoscopic transpapillary interventions in the treatment of choledocholithiasis.Interventions on the major duodenal papilla were performed in 286 patients with mechanical jaundice associated with choledocholiasis. The study population included 208 females and 78 males; mean age was 64 years; 72% of patients were older than 60 years.In 255 patients (87.7%) with relatively small (between 0.8 and 1.4 cm) single and multiple common bile duct stones, we managed to extract the concrements into the intestine during endoscopic procedures. Before that, all patients had undergone endoscopic papillotomy to facilitate subsequent stone extraction. The length of papillotomy incision depended on the size of the longitudinal fold, but did not exceed 6–8 mm. In 55 out of 256 patients, a nasobiliary drainage was installed in order to reduce mechanical jaundice and eliminate cholangitis.Nasobiliary drainage and common bile duct stenting improved patient condition and helped to prepare the patient for more radical endoscopic or surgical treatment.